The practice of exclusive breastfeeding among mothers attending a postnatal clinic in Tswaing subdistrict, North West province - U.A. Ahmadu-Ali; I.D. Couper (South African Family Practice)
Objectives: The aim of this study was to determine reported infant feeding practice with reference to exclusive breastfeeding, exclusive formula feeding and mixed feeding at six weeks postpartum among women attending a postnatal clinic in the Tswaing subdistrict of North West province, and the strength of the association between maternal human immunodeficiency virus (HIV) status and exclusive breastfeeding.